Ilustrasi Cerpen Majalah Mangle Periode April dan Mei 2010 Karya Agus Mulyana - Agus Triyadi (PANTUN, 2021)
Illustration as an integral part of a short story plays an important role in helping the reader'simagination to describe the scene in the story. Sundanese Mangle magazine is published for loyal readers, with a short story column with a variety of stories in a familiar Sundanese culture perspective. This Mangle illustration aims to provide reinforcement and to emphasize the content or narrative of the literary works. The illustrator, Agus Mulyana, visualizes the narrative in an informative way, with contrasting black and white characters. The illustrations are included in the type of naturalist illustration images which have the same shape and color as the reality or the actual situation (realist) existing in nature without any reduction or addition of the same shape as the actual situation. The appearance of Agus Mulyana's illustrations in short stories in Mangle Magazine as one of the local media loyal to Sundanese culture is a valuable contribution to the depiction of West Java. Narrating the history of Mangle Magazine from 1957 to 2021, it is appropriate that we preserve the documents of the illustrations and save them in the collection. More specially, it needs to be exhibited so that it becomes a Sundanese cultural asset.Keyword: Illustration, culture, Sundanese